A REVIEW OF ERGONOMICS TOWARDS PRODUCTIVITY - Gani, A Zuraini; Mohd Zamberi, Mahani; Md. Teni, Muhammad Hafizzuddin (International Journal of Supply Chain Management, 2018)
Nowadays often heard saying that ergonomics is one of the important things in improving the productivity of an industry. Ergonomic work culture must be applied in work space because reducing accident, injury, illness and the cost of treating employees and this can increase worker productivity thus give profit to the organization. Environmental ergonomics includes several factors such as lighting, thermal comfort, vibration, emotional and psychological needs of an individual. Psychological and physiological problems would increase stress levels and in turn affect the productivity of the organization. When employees feel stress and keep repeating the current situation they do the job, the potential of facing accident is high. In this research paper described ergonomic functions in the organization and also the relationship between ergonomics and productivity within an organization, At conclusion of the study the principles of ergonomics should be adopted and implemented by all sectors, especially in the industrial sector, to ensure that employees work safer, more comfortable, and healthier and productivity increased. It also can give a good impression, where employees work more efficiently in their workplace.